The Role of Emission Layer Morphology on the Enhanced Performance of Light‐Emitting Diodes Based on Quantum Dot‐Semiconducting Polymer Hybrids. Issue 18 (11th July 2016) - Fokina, Ana; Lee, Yeonkyung; Chang, Jun Hyuk; Park, Myeongjin; Sung, Younghun; Bae, Wan Ki; Char, Kookheon; Lee, Changhee; Zentel, Rudolf
Abstract : The influence of the morphology of quantum dot (QD)‐semiconducting polymer hybrid emission layers on the performance of quantum dot‐based light emitting diodes (QLEDs) is systematically investigated. Chemically grafted QD‐semiconducting polymer hybrids are fabricated by the ligand exchange procedure between CdSe/Cd x Zn1− x S QDs and a new block copolymer consisting of a carbazole‐based electroactive block with a low highest occupied molecular orbital level and a disulfide‐based anchor block. The performance of QLEDs with hybrid emission layers is compared with QLEDs utilizing QD‐only and physically mixed QD/polymer emission layers. It is shown that only in the emission layers formed by chemically grafted hybrids QDs are evenly distributed throughout the semiconducting polymer matrix. This leads to improved charge transport balance and suppressed photoluminescence quenching of QDs. As a result, hybrid QLEDs with the peak external quantum efficiency of 5.6% and the peak luminance of 21 707 cd m −2 which outperform the conventional devices with QD‐only emission layers are fabricated. Abstract : Quantum dot‐based light‐emitting diodes (QLEDs) with hybrid quantum dot‐semiconducting polymer emission layers, which surpass the efficiency and brightness of the conventional QLEDs are developed. Their superior properties are a result of the morphology of the hybrid emission layer, which influences charge carrier transport and photoluminescence properties of the devices positively.